Avian Infectious Bronchitis Virus - ODEND'HAL, STEWART (The Geographical Distribution of Animal Viral Diseases, 1983)
This chapter provides an overview of the classification, description, hosts, key developments, diagnostic techniques, and diagnostic reagents for avian infectious bronchitis virus. Avian infectious bronchitis virus belongs to the family Coronaviridae; genus Coronavirus; and species Avian infectious bronchitis virus. The virus causes acute contagious respiratory illness and includes reproductive tissue disease in chickens. The hosts of avian infectious bronchitis virus are only chickens. Avian infectious bronchitis disease was first reported in the United States. Vaccines for this disease were developed in the 1950s and the economic impact diminished. The diagnostic techniques for avian infectious bronchitis virus are virus neutralisation (VN), agar gel immunodiffusion (AGID), fluorescent antibody (FA), compliment fixation (CF), and enzyme-linked immunosorbent assay (ELISA).